Experimental Investigation of Flow Control over an Ahmed Body using DBD Plasma Actuator - S. Shadmani; S. M. Mousavi Nainiyan; M. Mirzaei; R. Ghasemiasl; S. G. Pouryoussefi (Journal of Applied Fluid Mechanics, 2018)
Ahmed body is a standard configuration of road vehicles and most of the studies of automobile aerodynamics are performed based on it. In this paper, the plasma actuator was used as an active flow control method to control the flow around the rear part of the Ahmed body with the rear slant angle of 25°. Experiments were carried out in a wind tunnel at two different velocities of U=10m/s and U=20m/s using steady and unsteady excitations. The hot-wire anemometer was used to measure the vortex shedding frequency at the downstream of the body. Pressure distribution was measured using 52 sensors and total drag force was extracted with a load cell. Furthermore, smoke flow visualization was employed to investigate the flow pattern around the body. The results showed that the plasma actuator was more effective on the pressure distribution and total drag force at the velocity of U=10m/s. In fact, by applying steady and unsteady excitations there was 7.3% and 5% drag reduction; respectively. While at the velocity of U=20m/s; the actuator had no significant effect on pressure distribution and total drag. As a remarkable result, the plasma actuator, especially in the steady actuation, has demonstrated its effectiveness on dispersing the longitudinal vortices and suppressing the separated flow on the rear slant at low velocities.